2023
DOI: 10.2147/opth.s417821
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Replicates of Intraocular Inflammatory Biomarkers in Ocular Fluid Samples Analyzed with Multiplex Assays

Daniel Lamoureux,
David Wong,
Tina Felfeli

Abstract: Certain factors such as instrumental and sample processing errors may contribute to variability of ocular biofluid samples when they are run as replicates with multiplex assays. There is a paucity of literature on the variability of replicates in multiplex assays. This study aims to evaluate whether there is significant variability in replicate analyses of multiplex assays. Methods: A total of 152 human ocular biofluid samples (51 aqueous humor and 101 vitreous) were collected and assayed for 27 cytokine bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…We have previously demonstrated that some variability may be noted in replicate analyses of biomarkers most notably in vitreous samples. 19 It has been shown that using multiplex assay kits from different companies may show varying cytokine concentrations. 20 21 While comparison of quantification is not ideal between multiplex assay kits from differing companies, trend analysis may still be appropriate by evaluating cytokine trends from serial samples.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that some variability may be noted in replicate analyses of biomarkers most notably in vitreous samples. 19 It has been shown that using multiplex assay kits from different companies may show varying cytokine concentrations. 20 21 While comparison of quantification is not ideal between multiplex assay kits from differing companies, trend analysis may still be appropriate by evaluating cytokine trends from serial samples.…”
Section: Discussionmentioning
confidence: 99%